2007
DOI: 10.1534/genetics.107.074708
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase I-Dependent Viability Loss in Saccharomyces cerevisiae Mutants Defective in Both SUMO Conjugation and DNA Repair

Abstract: Siz1 and Siz2/Nfi1 are the two Siz/PIAS SUMO E3 ligases in Saccharomyces cerevisiae. Here we show that siz1D siz2D mutants fail to grow in the absence of the homologous recombination pathway or the Fen1 ortholog RAD27. Remarkably, the growth defects of mutants such as siz1D siz2D rad52D are suppressed by mutations in TOP1, suggesting that these growth defects are caused by topoisomerase I activity. Other mutants that affect SUMO conjugation, including a ulp1 mutant and the nuclear pore mutants nup60D and nup13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 72 publications
4
49
0
Order By: Relevance
“…This link between WSS1 and genome maintenance may be related to the fact that wss1⌬ mutants display severe synthetic-fitness defects in the absence of the Sgs1 DNA helicase (37,49). The notion that SUMO plays a role in DNA damage repair is not new, given that the loss of a number of general SUMO regulators results in sensitivity to DNA-damaging agents (4,8,9,26,31). However, unlike ulp2⌬ mutants, for example, wss1⌬ mutants do not display obvious growth defects or a large number of synthetic-fitness interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This link between WSS1 and genome maintenance may be related to the fact that wss1⌬ mutants display severe synthetic-fitness defects in the absence of the Sgs1 DNA helicase (37,49). The notion that SUMO plays a role in DNA damage repair is not new, given that the loss of a number of general SUMO regulators results in sensitivity to DNA-damaging agents (4,8,9,26,31). However, unlike ulp2⌬ mutants, for example, wss1⌬ mutants do not display obvious growth defects or a large number of synthetic-fitness interactions.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the increased levels of Top1 upon copper induction are a consequence of protein stability rather than increased gene expression. Since Top1 is known to be sumoylated under certain conditions (Mao et al 2000;Chen et al 2007) and SUMO modification can stabilize proteins (de Cristofaro et al 2009), we explored whether SUMO post-translational modification plays any role in Top1 stability in ESCRT mutants.…”
Section: The Escrt Complexmentioning
confidence: 99%
“…To explore the effect of Top1 SUMOylation at natural acceptor sites on the protein, we expressed an active-site tyrosine substitution allele (top1-Y 727 F-top1-YF), since SUMOylated levels of this mutant protein are elevated (Chen et al 2007). Chen and colleagues also found that much of the SUMOylation occurs on three lysine residues (K65, K91, K92).…”
Section: The Escrt Complexmentioning
confidence: 99%
“…We recently reported that a siz1⌬ siz2⌬ rad52⌬ strain is nearly inviable, but that its growth defect is suppressed by deleting the gene encoding topoisomerase I (TOP1; Chen et al, 2007). This phenotype is independent of 2 m and is observed in strains both containing (cir ϩ ) and lacking (cir°) 2 m. However, this set of mutations also showed a separate effect on 2 m accumulation.…”
Section: Hrr Is Required For 2 M Hyperamplification In Siz1⌬ Siz2⌬mentioning
confidence: 99%
“…Ulp1 is also required for maturation of the SUMO precursor and so participates in both SUMO conjugation and deconjugation. Mutants in certain nuclear pore complex (NPC) and nuclear envelope proteins also have sumoylation defects because they mislocalize Ulp1 (Zhao et al, 2004;Chen et al, 2007;Lewis et al, 2007;Palancade et al, 2007). Recently, a factor that acts downThis article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E08 -06 -0659) on December 24, 2008. stream of sumoylation has been identified: a heterodimer consisting of Slx5/Hex3, and Slx8 acts as a ubiquitin ligase that targets sumoylated proteins for ubiquitin-dependent proteolysis (Ii et al, 2007a;Prudden et al, 2007;Sun et al, 2007;Uzunova et al, 2007;Xie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%